ANALISIS PENGELOLAAN KAS DAERAH SEBAGAI UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH (Studi di Pemerintah Kota Padang Panjang Tahun 2010) - , Rafni Yenti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aim is to analyze cash management in the City Governmant of Padang Panjang, to identify potencies unused for managing the local cash, and to determine magnitude of local increased income potency through the cash managemen. In terms of optimizing the empowerment of idle cash is done through a portfolio based on the interest rate on Bank Nagari, BNI, BRI and BSM as well as take advantage of future tax payments. Data used in this study were primary and secondary data.The former were data of interviews, the latter were data APBD realization of the City Government of Padang Panjang in 2010, monthly report of APBD realization of the City Government of Padang Panjang in 2010, and interest rate of bank, as well as early balance sheet og the City Government of Padang Panjang in 2010.Analytical methods used in this study were quantitative and qualitative methods. For a quantitative method using a formula approach to the cash budget according to the concept of Building Institutions for Good Governance (BIGG) 2002, the formed used data of inflow and outflow cash data og monthly report of APBD realization as basic cash budget arrangement. Idle cash might be found by reducing final cash banlance by minimal cash balance as reserves.The latter was to know the perception of officials and legislators in the city of Padang Panjang application of cash management as an alternative to increase revenue. Based on results of data analysis, it could be found that the City Government of Padang Panjang was able to increase Local Original Income (PAD) without incurring society and breaking law, be obtained by optimizing the potential income from the utilization of idle cash through short-term investments in the form of deposits / DOC for 2010 was Rp8.165.193.503. Results of these studies show that cash management has the potential to increase PAD